Impact of heterogeneity-corrected dose calculation using a grid-based Boltzmann solver on breast and cervix cancer brachytherapy - Hofbauer, Julia (J Contemp Brachytherapy, 2016)
PURPOSE: To analyze the impact of heterogeneity-corrected dose calculation on dosimetric quality parameters in gynecological and breast brachytherapy using Acuros, a grid-based Boltzmann equation solver (GBBS), and to evaluate the shielding effects of different cervix brachytherapy applicators. MATERIAL AND METHODS: Calculations with TG-43 and Acuros were based on computed tomography (CT) retrospectively, for 10 cases of accelerated partial breast irradiation and 9 cervix cancer cases treated with tandem-ring applicators. Phantom CT-scans of different applicators (plastic and titanium) were acquired. For breast cases the V(20Gyαβ3) to lung, the D(0.1cm(3)), D(1cm(3)), D(2cm(3)) to rib, the D(0.1cm(3)), D(1cm(3)), D(10cm(3)) to skin, and D(max) for all structures were reported. For cervix cases, the D(0.1cm(3)), D(2cm(3)) to bladder, rectum and sigmoid, and the D(50), D(90), D(98), V(100) for the CTV(HR) were reported. For the phantom study, surrogates for target and organ at risk were created for a similar dose volume histogram (DVH) analysis. Absorbed dose and equivalent dose to 2 Gy fractionation (EQD2) were used for comparison. RESULTS: Calculations with TG-43 overestimated the dose for all dosimetric indices investigated. For breast, a decrease of ~8% was found for D(10cm(3)) to the skin and 5% for D(2cm(3)) to rib, resulting in a difference ~ –1.5 Gy EQD2 for overall treatment. Smaller effects were found for cervix cases with the plastic applicator, with up to –2% (–0.2 Gy EQD2) per fraction for organs at risk and –0.5% (–0.3 Gy EQD2) per fraction for CTV(HR). The shielding effect of the titanium applicator resulted in a decrease of 2% for D(2cm(3)) to the organ at risk versus 0.7% for plastic. CONCLUSIONS: Lower doses were reported when calculating with Acuros compared to TG-43. Differences in dose parameters were larger in breast cases. A lower impact on clinical dose parameters was found for the cervix cases. Applicator material causes systematic shielding effects that can be taken into account.